2012
DOI: 10.35197/rx.08.01.2012.05.af
|View full text |Cite
|
Sign up to set email alerts
|

Una estrategia institucional en la prevención de la muerte materna en el estado de Guerrero, México

Abstract: En este trabajo se reflexiona acerca de las acciones emprendidas en materia de prevención de la mortalidad materna en el nivel local por dos agentes: el gobierno guerrerense a través de la Secretaría de la Mujer y la participación activa de cuatro organizaciones sociales comprometidas con la lucha por una maternidad digna, segura y placentera. Interesa dar cuenta de los alcances y las expectativas de un programa ejecutado a partir del año 2005 y hasta el año 2009. Particularmente, se demuestra que la alianza e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 18 There is tension between traditional practices and official health services 19 despite constitutional recognition of indigenous rights and local initiatives to facilitate collaboration. 20 Earlier research found that fear of episiotomies and c-sections made indigenous women unwilling to have institutional childbirths. 21 Distance to or absence of official health services were additional barriers.…”
Section: Introductionmentioning
confidence: 99%
“… 18 There is tension between traditional practices and official health services 19 despite constitutional recognition of indigenous rights and local initiatives to facilitate collaboration. 20 Earlier research found that fear of episiotomies and c-sections made indigenous women unwilling to have institutional childbirths. 21 Distance to or absence of official health services were additional barriers.…”
Section: Introductionmentioning
confidence: 99%